The evaluation of the therapeutic potential of hesperetin on diethylnitrosamine and phenobarbital induced liver injury in rats - Kisacam, Mehmet Ali; Kocamuftuoglu, Gonca Ozan; Tektemur, Nalan Kaya; Ozan, Penbe Sema Temizer (Ankara Univ, 2022)
Nitrite and amine reactions can occur rapidly and produce nitrosamines, in-vivo. Diethylnitrosamine (DEN) and phenobarbital (PB) are readily inducing liver injury and hesperetin (HES), as a flavonoid found in citrus fruits, have the potential to compensate for their harmful effects. In this study, the therapeutic effects of HES were evaluated in DEN and PB mediated liver defect. Adult male Sprague-Dawley rats were split into 5 groups (n=10): Control, DEN, DEN+PB, HES, and DEN+PB+HES. 150 mg/kg DEN was applied intraperitoneally to DEN groups. Fifteen days after the DEN application 500ppm of PB was given in drinking water. HES were administered at 50 mg/kg dose orally for 8 weeks. Blood and liver malondialdehyde (MDA), glutathione (GSH) levels, and catalase (CAT), superoxide dismutase (SOD) activities were measured spectrophotometrically. Moreover, histologic examination of liver sections and apoptosis were determined with hematoxylin-eosin and TUNEL methods, respectively. DEN-PB application was found to increase blood and liver MDA levels and liver CAT activity, oppositely, decreased blood and liver SOD activity, GSH levels, and blood CAT activity. HES was found to have a positive impact on oxidative stress parameters by decreasing liver and blood MDA activity, increasing blood CAT and SOD activity together with liver GSH levels and SOD activity. Whereas DEN and PB application increased all histopathological findings and TUNEL positive cells, HES administration decreased these findings which might be important for the protection of liver cell structure from cell damage. These results suggest that HES administration could be an alternative therapeutic approach to liver damage.
Hesperetin'in, sıçanlarda dietilnitrozamin ve fenobarbital kaynaklı karaciğer hasarı üzerindeki terapötik potansiyelinin değerlendirilmesi
Keywords: Apoptosis; diethylnitrosamine; hesperetin; oxidative stress; phenobarbital